Pemanfaatan Google Form sebagai Media dalam Asesmen Formatif di Kelas XII IPS SMA Negeri 9 Semarang - Tetti Kusuma Widyawati; Asep Purwo Yudi Utomo; Fajar Fitra Dewi; Daniyar Rohman (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Students at the high school level are currently generation Z or often referred to as the digital generation because they have a dependence on technology. The solution that can be implemented so that students are focused and interested in learning is to utilize each student's device for the learning process. Google Form is one of the right choices as a learning medium such as in formative assessment. This study aims to describe the use of the Google form as a medium for formative assessment with the research sample being class XII IPS at SMA Negeri 9 Semarang. This study uses a descriptive quantitative approach with the experimental method. The results of this study are (1) 44.45% of students do the formative assessment maximally without the media google form. 90.91% of students do the formative assessment optimally by utilizing the Google form media. This shows that the use of the Google form as a medium in formative assessment has an influence on student learning outcomes. Student learning outcomes increased by 46.46%. (2) In terms of process and time, the use of google form is more effective than without google form. Students can use the time to discuss without fear of taking a long time to write answers. This provides the effectiveness of students in discussing and understanding related opinions and facts in articles.